Detecting Gender Discrimination in University Salaries: A Case Study - Swartzman, Leora C.; Seligman, Clive; McClelland, Wlliam J. (Canadian Journal of Higher Education, 1992)
To assess sex discrimination in university salary allocation accurately, one must determine whether gender explains the salary difference in and of itself, or exerts its influence through other variables, such as rank and departmental affiliation, that themselves affect salary and may correlate with gender. Using members of the Faculty of Social Science (N = 133) of a large Canadian university as a case sample, we assessed gender discrimination in promotion and gender differences in departmental affiliation as related to salary before including these two variables in statistical analyses predicting salary. No evidence was found for discrimination in promotion and women were not morie under-represented in the higher-salaried departments. Several regression models recommended in the literature for assessing gender discrimination in salaries were conducted and yielded convergent findings : male and female faculty similar on salary-relevant variables were equivalently paid. While these results should be reassuring, they would not go very far toward resolving salary discrimination disputes in the university studied or in most other academic institutions. The difficulties of applying the results of statistical analyses within a politically-charged arena are discussed.